Elaboration and microbiological quality of kookies biscuits with quinoa and oat flour addition (Research, Society and Development, 2020)
The present research had as objective to elaborate cookies type cookies, with addition of different concentrations of the flour of the quinoa and oats and to analyze the microbiological quality. Flours and other inputs used in the preparation of cookies were purchased from local businesses in the city of Pombal, Paraíba, Brazil. The results obtained from the microbiological analyzes, the samples prepared with the addition of different concentrations of quinoa and oat flour, presented satisfactory results in relation to thermotolerant coliforms (coli at 45 ° C), that is, the samples are in accordance with the standards of quality for this microbiological parameter. For coagulase positive Staphylococcus samples 1.25% FQFA and 2.5% FQFA showed values with a slight change from what is allowed by the legislation and for the other samples, the values obtained are in accordance. In relation to Salmonella ssp, all formulations analyzed showed absence of this bacterium, that is, the results were satisfactory, since this bacterium is related to a good part of the infections caused by food.